DAPATKAH SITUS JEJARING SOSIAL MENDORONG INTENSI BERWIRAUSAHA HIJAU? - Yoel Christianto Raharjo; Chrisanty Victoria Layman (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- Social networking sites are an important aspect of everyday life. Social networks are also thought to have the power to increase the intention of green entrepreneurship which is important in preventing ecological deprivation. Therefore, this study aims to analyze the effect of social networking sites on the green entrepreneurship intentions of Jabodetabek students mediated by self-efficacy and risk-taking tendencies. This research was conducted using quantitative research methods, with the use of convenience sampling and electronic questionnaires as data collection methods from 181 students studying at universities in the Jabodetabek area. Data analysis was performed using PLS-SEM. The results showed that social networking sites had a significant effect on green entrepreneurship intentions directly, without being mediated by self-efficacy or risk-taking tendencies. Thus, there is great hope that social networking sites can be utilized in the realization of green growth. Through the social networking movement that raises awareness and insight into the green economy, it can have a direct effect on increasing the green entrepreneurship intentions of Jabodetabek students. Keywords: Social Networking Sites; Self-Efficacy; Propensity to Take Risks, Green Entrepreneurship Intentions